Entre conflits et pouvoir : le rôle des Africaines-Américaines dans la création des associations féminines noires (1890-1960) - Christine Dualé (Anglophonia)
From the very beginning, the racial hierarchy structured African American women’s lives. They were persuaded they were inferior beings thus, they integrated such incapacity. By reacting against gendered violence slave women and former slaves created a dynamic that allowed them to take their oppression as Black beings and as females into account. Then, by the end of the nineteenth century, the creation of the first black women’s clubs gave them more opportunities to enlarge their first objectives.The creation of black women’s clubs brought them respectability while improving their lot. But their fight was not immune from conflicts with women themselves and with black males. While producing new definitions of themselves, they also created new tools of resistance. Therefore, all these aspects will allow us to deal with the themes of power and conflict as positive elements and to consider African American women as the mistresses of their lot and not as victims anymore.